Targeting antimicrobial restriction: outcomes of pharmacist-led stewardship interventions at the university hospital Salzburg. - Past, Eva; Hartmann, Laura; Zimmermann, Robert; Zimmermann, Georg; Wallner, Markus; Walter, Lisa; Porsche, Ulrike; Kern, Jan Marco (Infection, 2025)
Purpose: Antimicrobial overuse and misuse remain critical challenges. This study examined pharmacist-led post-prescription interventions targeting restricted antimicrobials in a university hospital, identifying underlying drug-related problems (DRPs), their clinical relevance, economic impact and characteristic patterns of inappropriate use. Methods: A retrospective observational analysis (January– December 2022) was conducted at the Salzburg State Hospitals using routine data of pharmacist-led interventions on restricted antimicrobials. DRPs and intervention types were categorized using validated criteria. Clinical relevance was independently assessed through an external survey, and interrater reliability was determined to ensure consistency in classification and evaluation. Potential cost savings and acceptance rates of the pharmaceutical interventions were assessed. Results: A total of 3897 restricted antimicrobial prescriptions were analyzed, with 11.7% (456) showing at least one DRP in 366 patients. The majority of DRPs (80.2%) exhibited marked clinical relevance, mainly due to non-conformance with guidelines (27.4%), unclear indication (27.2%), and the need for patient or drug monitoring (12.5%). Broad-spectrum agents linezolid (25.0%), meropenem (24.1%), ciprofloxacin (15.8%), and piperacillin-tazobactam (8.8%) accounted for nearly 74% of all DRPs. DRP-related interventions aimed at optimizing PK/PD parameters (30.6%), treatment discontinuation (28.1%), and de-escalation (17.9%). The acceptance rate of interventions was high (82.7%). A cost reduction potential was identified in 89.7% of interventions, saving €180,420 in avoided drug expenses. Conclusion: Pharmacist-led post-prescription interventions within an established AMS program effectively identified clinically relevant misuse of restricted antimicrobials. Targeted actions on key agents enable high-impact optimization, supported by strong acceptance and cost-saving potential - thereby enhancing stewardship efforts, guiding improvements in diagnostics, and prescribing behavior.